"Water Politics": Gampong Lengkong Existence in Langsa City 2000-2021 - Okhaifi Prasetyo; Dyah Kumalasari (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2021)
Water is a natural resource that has a very important function for the life of living things on earth. The existence of Gampong Lengkong has brought its own changes since 2000 after the existence of a clean water industry by managing clean water that is in the ground. This study aims to obtain a complete and integrated understanding of the clean water household industry in Gampong Lengkong, Langsa City, which affects the community both in terms of politics and existence. Using qualitative methods with data collection techniques literature study, observation, interviews, documentation. Based on the research results, it is concluded as follows: In 1995 marked the emergence of a water industry being developed in an area which is a peat land area, the Gampong Lengkong area was developed into a small household industrial area. At this early stage the area did not exploit so many clean water. In its existence, the people of Gampong Lengkong are greatly helped by the clean water industry. Besides, there is a political element in every policy taken for the implementation of economic activities in Lengkong Village. Political activity is characterized in three dimensions, namely: activity, decision making, and distribution of clean water.